Exploring Digital Green Waqf through Systematic Literature Review: Toward Sustainable Islamic Finance - Wali Saputra (Indo Publishing, 2026)
Digital transformation and the growing urgency for environmental sustainability have driven innovation within Islamic finance, including the revitalization of the waqf institution. The concept of Digital Green Waqf emerges as a convergence of waqf digitalization, environmental sustainability principles, and maqasid shariah (the objectives of Islamic law). However, comprehensive understanding and empirical exploration of this concept remain limited. This study aims to explore the concept of Digital Green Waqf through a systematic literature review (SLR) to identify research trends, implementation models, benefits, challenges, and research gaps within the context of sustainable Islamic finance. The SLR was conducted across six major academic databases—Scopus, Web of Science, IEEE Xplore, Google Scholar, ProQuest, and Emerald Insight—covering publications from 2015 to 2024. Out of 156 identified articles, 32 met the inclusion criteria and were analyzed using thematic analysis, content analysis, and gap analysis approaches. The literature analysis identified four main models of Digital Green Waqf: Crowdfunding platforms for green projects, Blockchain-based carbon credit waqf, AI-powered sustainable waqf management, and Digital twin technology for monitoring green waqf assets. Digitalization of waqf has been shown to improve accessibility by up to 300%, transparency by 85%, and management efficiency by 45–60%. Meanwhile, green waqf initiatives have contributed to a 35% reduction in carbon emissions and a 40–60% increase in community income. However, only 28% of the reviewed articles explicitly addressed the integration of digitalization and environmental sustainability, indicating that this area is still emerging. The main challenges identified include the digital divide, limited regulatory frameworks, human resource capacity, and trust issues in digital platforms. The findings suggest that Digital Green Waqf represents an innovative frontier in Islamic finance, offering transformative potential for mobilizing community resources toward sustainable development. The proposed conceptual framework integrates shariah principles, digital technologies, and sustainability principles into four interrelated layers: foundation, enablers, implementation, and outcomes. Future research should focus on empirical studies, longitudinal impact assessments, behavioral analyses, and the development of regulatory frameworks that support sustainable innovation within the Digital Green Waqf ecosystem.